Memahami Konsep Dasar Gerak, Bentuk Dan Ukuran Bumi Studi Analisis Kitab Al-Qȃnȗn Al-Mas'ȗdȋ Karya Al-Biruni Dalm Konteks Hukum Islam - Sakirman Sakirman (Institut Agama Islam Negeri Curup, 2017)
The central point of a scientist is imprinted on the contribution that can be given to his people. Because, the work that was born of a scientist is a reference that never died was referred by the next scientist in order to complete the methodological study that has not been explored. Al-Biruni, was one of the most admired scientists of his time, especially in the study of astronomy. In 1030 AD, al-Biruni wrote an astronomical encyclopedia entitled Al-Qȃnȗn Al-Mas'ȗdȋ In one of these works, al-Biruni attempted to integrate and interconvert classical astronomical ideas with modern astronomy. The work that became his magnumopus, is still the main reference of astronomers. In brief, Al-Qȃnȗn Al-Mas'ȗdȋ eborate about the intricacies of modern astronomical studies, because in mathematical studies al-Biruni already using the calculation of higt accuration. One of them is the study of basic, motion, shape and size of the earth. According to the thought of al-Biruni as poured in Al-Qȃnȗn Al-Mas'ȗdȋ , al-Biruni proves that the shape of the earth is round, the earth revolves around the sun and the moon rotates by its spin around the earth. Based on the above assumption, al-Biruni can be equated with modern astronomy. Because in his thinking, al-Biruni tried to dismiss the study of astronomy with an astrological methodology.